The Export Supply Model of Bangladesh: An Application of Cointegration and Vector Error Correction Approaches - Toy, Mahmudul Mannan; Moniruzzaman, MD.; Hassan, A. B. M. Rashedul (International Journal of Economics and Financial Issues, 2011)
The broad objective of this study is to empirically estimate the export supply model of Bangladesh. The techniques of cointegration, Engle-Granger causality and Vector Error Correction are applied to estimate the export supply model. The econometric analysis is done by using the time series data of the variables of interest which is collected from various secondary sources. The study has empirically tested the hypothesis, long run relationship and casualty between variables of the model. The cointegration analysis shows that all the variables of the study are co-integrated at their first differences meaning that there exists long run relationship among the variables. The VECM estimation shows the dynamics of variables in the export supply function and the short run and long run elasticities of export supply with respect to each independent variable. The error correction term is found negative which indicates that any short run disequilibrium will be turned into equilibrium in the long run. Keywords: Engine of Growth; Cointegration; Granger Causality; VECM, VAR; Impulse Response. JEL Classifications: F4